The House of Wisdom - Edward F Rossomando (Wolters Kluwer Medknow Publications, 2011)
This is an editorial less about science and more about history of science. Professor Al-Khalili shows in clear and conversational prose how the Muslims and those in the Islamic world not only kept Greek science alive while Europe in chaos but contributed to it in ways that facilitated many discoveries by European scientists centuries later.